Comparative study of continuous method and interrupted method of episiotomy in terms of healing of the surgical wound - Khatri, Rahul; Jain, Bhoomika; Mhapankar, Sabrina; Kumar, Sushil (Clinical Journal of Obstetrics and Gynecology, 2021)
Episiotomy is a most commonly performed minor procedure. There are various type of episiotomy suturing, in this study two most common types of episiotomy suturing techniques were compare in terms of healing rate. This study concluded that the continuous method of episiotomy suturing is although faster, cosmetically better and associated with less post-operative pain but it heals significantly better than interrupted method of suturing.